The Menace of Non-Being: On Nestle Waters' Plunder and Jürgen Moltmann's Sabbath Peace - Herrmann, Leslie ca. 20./21. Jh. (Journal of religious ethics, 2020)
In the face of unremitting faith in economic progress and the attendant environmental degradation that is, increasingly, one of its ugly fruits, Jürgen Moltmann's rich conception of God's Sabbath peace offers a compelling reorientation. When drawn upon for its contribution toward the fostering of one’s moral imagination and for the cultivation of ethical criteria, it offers an accessible yet rigorous lens through which to view a particular situation: the attempt by Nestlé Waters to build the largest bottled water plant in North America. The author finds within Moltmann’s vision a way to critically assess the project, critique the underlying foundations of its character, and offer alternatives for seeking the flourishing of the whole of God’s creation.